Insomnia Is Associated With Frequency of Suicidal Ideation Independent of Depression: A Replication and Extension of Findings From the National Health and Nutrition Examination Survey - Simmons, Zach; Erickson, Lance D.; Hedges, Dawson; Kay, Daniel B. (Frontiers in Psychiatry, 2020)
Objective: Insomnia is associated with suicidality, although the mechanisms of this association are unclear. This study sought to replicate previous findings showing that insomnia but not sleep duration is associated with suicidal ideation in adults. We further investigated whether sleep duration moderated the association between insomnia and suicidal ideation. Material and Methods: We used the 2005-2006 cycle of the National Health and Nutrition Examination Survey to replicate previously reported findings from the 2007-2008 cycle. We further replicated this analysis in combined data from the 2005-2006 and 2007-2008 cycles. We used ordered logistic regression to determine whether insomnia was associated with frequency of suicidal ideation independently of depression and other potential confounds. To extend these findings, we used the combined 2005-2006 and 2007-2008 cycles to test whether sleep duration or depression moderated the association between insomnia and suicidal ideation. Results: This study replicated previous results showing that insomnia is associated with suicidal ideation even after adjusting for potential confounding variables, including depression. Sleep duration did not moderate this association. Conclusions: In this study, we found that insomnia might be uniquely associated with frequency of suicidal ideation. This association cannot be explained by the shared association with sleep duration or depression.